Efek Mediasi Motivasi Kerja pada Pengaruh Budaya Organisasi dan Kepemimpinan Transformasional terhadap Kinerja Karyawan - Melitina Tecoalu; Hery Winoto Tj.; Susy Susy (BUDGETING : Journal of Business, Management and Accounting, 2022)
This study aims to determine the mediating effect of work motivation on the influence of organizational culture and transformational leadership on employee performance. This research method is descriptive quantitative. The population in this study were all education personnel at the Trisakti School of Insurance Management (STMA), Jakarta, totaling 36 (thirty six) people and all members of the population. This study uses a Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS) using SmartPLS 3.3 software. This research is a census research. The results showed that all indicators used in this study were valid and reliable. In conclusion, organizational culture, transformational leadership, and work motivation affect employee performance. Also, work motivation has a role in mediating the influence of organizational culture on employee performance. However, it does not mediate the effect of transformational leadership on employee performance. Keywords: Organizational Culture, Transformational Leadership, Employee Performance, Employees, Work Motivation, Education Personnel